Studi Kasus Pengaruh Tower Seluler terhadap Penerimaan Siaran Televisi Daerah Padat Penduduk di Jalan Buring Dalam pada Kecamatan Klojen Kota Malang - Patricia Alfira Jokhanan; Koesmarijanto Koesmarijanto; Hudiono Hudiono (Politeknik Negeri Malang, 2021)
This study aims to analyze the effect of cell towers on the quality of TV broadcast reception in densely populated areas located on Jalan Buring Dalam Klojen District, Malang City. The results of this study are an analysis of the effect of the obstacle with the type of cellular tower on analog TV signaling, by comparing the measurement results and calculations obtained from the calculation of field strength received using the damping calculation based on Recommendation ITU-R P.1546-1 with the Okumura Hata method, and knife edge diffraction theory. In conclusion, the measurement results in the presence of cellular obstacle towers obtained an average difference between the Line of Sight and With Obstacle of 2,6525 dB with an obstacle distance of 15 m from the measurement point, and 4.548571 dB with a distance of 40 m. Estimated attenuation value - influenced by cellular tower diffraction with obstacle distance of 15 m from the measurement point of 41,1088 dB, and with a distance of 40 m of 36.67143 dB. The value of cellular tower attenuation based on measurements for the distance of 15 m from the obstacle obtained values of 2.6525 dB and for the calculation of 41,1088 dB Whereas the value of the cellular tower attenuation based on the measurement results for a distance of 40 m has an average of 4.548571 dB and for the calculation of 36.67143 dB.